City Noise-Air : an environmental quality index for cities - Silva, Lígia Torres (2012)
Global population growth has led to an increase of the number of people living in urban areas. As a consequence, stresses on space, ecosystems, infrastructures, facilities and personal lifestyles have been enhanced. Problems related to the quality of life in cities are increasingly relevant, especially with regard to environmental issues. Domestic and industrial sources and, primarily, motorised traffic are responsible for pollutant emissions and noise that decisively affect life in modern cities. In this context, evaluating and monitoring urban environmental quality has become an important issue for decision making and planning of more liveable and sustainable cities. Computational simulation models for the phenomena associated with emission and propagation of noise and dispersion of air pollutants were applied within a GIS platform to generate maps of noise and pollutant concentrations. This paper presents an urban environmental quality index: City Noise-Air. In case either one of the environmental conditions (pollutants or noise level) exceeds the accepted limit, the City Noise-Air index will reflect that exceedance and thus equals zero (red). If there is no limit violation, then City Noise-Air incorporates all of the selected conditions into an overall quality index by a multi-criteria combination that allows trade-offs. A case study is presented for Viana do Castelo, a mid-sized Portuguese city, in which City Noise- Air values were calculated taking in consideration the noise level (Lden) and the concentrations of CO, NO2, O3, C6H6 and PM10.